Partisipasi Publik dalam Penyusunan Dokumen Analisis Dampak Lingkungan Pasca Berlakunya Undang-Undang/Perppu Cipta Kerja - Melisa Ayu Azhara; Siti Ruhama Mardhatillah (Fakultas Hukum Universitas Islam Indonesia, 2023)
The Job Creation Law (which has been revoked by Government Regulation in lieu of Law (Perpu) Number 2 of 2022) is a government effort to overcome overlapping regulations to increase investment. This research raises two problem formulations: First, how does the Job Creation Law/Perpu regulate the principle of public participation, particularly in the preparation of the Environmental Impact Assessment (EIA/AMDAL) documents. Second, how does the Job Creation Law/Perpu regulate the role of environmental organizations and what is the urgency of the role of environmental organizations in preparing the AMDAL? This is a normative legal research using literature study methods, qualitative descriptive data analysis methods, as well as conceptual and statutory approaches. The results of the study concluded that, Article 26, Article 39 paragraph (1) and paragraph (2), as well as Article 63 paragraph (1) in the Job Creation Law/Perpu reduce aspects of public participation which had previously been regulated quite well in Law Number 32 of 2009 on Environmental Protection and Management (UU PPLH). The urgency of the role of environmental organizations in preparing the AMDAL is to provide advice and input for the implementation of environmental protection in business activities.Keywords: Public Participation; Environmental Impact Assessment, Job Creation Law/Perppu AbstrakUU Cipta Kerja (yang telah dicabut dan diganti dengan Perpu Nomor 2 Tahun 2022) merupakan suatu usaha pemerintah mengatasi tumpang tindih peraturan untuk meningkatkan investasi. Penelitian ini mengangkat dua rumusan masalah: Pertama, bagaimana UU/ Perpu Cipta Kerja mengatur prinsip partisipasi publik, khususnya dalam penyusunan dokumen AMDAL. Kedua, bagaimana UU Perpu Cipta Kerja mengatur peran organisasi lingkungan dan apa urgensi peran organisasi lingkungan dalam penyusunan AMDAL? Penelitian ini adalah penelitian hukum normatif dengan menggunakan metode studi literatur, metode analisis data deskriptif kualitatif, serta pendekatan konseptual dan perundang-undangan. Hasil penelitian menyimpulkan bahwa, Pasal 26, Pasal 39 ayat (1) dan ayat (2), serta Pasal 63 ayat (1) dalam UU Perpu Cipta Kerja mengurangi aspek partisipasi publik yang sebelumnya telah diatur dengan cukup baik dalam UU Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup (UU PPLH). Adapun urgensi peran organisasi lingkungan hidup dalam penyusunan AMDAL adalah untuk memberikan saran dan masukan bagi terselenggaranya perlindungan lingkungan hidup dalam aktivitas usaha.Kata-kata Kunci: Partisipasi Publik; Analisis Dampak Lingkungan, Undang-Undang/ Perppu Cipta Kerja